Public Procurement Reform in Iraq : A Long and Difficult Road - Ali, Nazaneen Ismail; Jacobs, Andrew; Lipson, Rachel; Isoldi, Fabio (World Bank, Washington, DC, 2014)
Over the course of a six-year period from 2006-2011, the Government of Iraq (GOI), with support from the World Bank, undertook an ambitious effort to reform its public procurement system and legal framework. Among other actions, an Inter-Ministerial Task Force (IMTF) was created, consultations were held with civil society and the private sector, and a comprehensive new law was drafted based on international best practices. In some ways, the challenges to reforming Iraq's public procurement system mirror the usual obstacles in implementing public sector reforms. However, given the country context, this case also presents unique and important lessons that helped inform future-decision making on public procurement reform in other conflict states. Finally, the Iraqi experience showed the importance of adapting gradual fixes in tackling institution building. While maintaining a long-term vision is important, it becomes critical in a post-conflict environment to demonstrate early results. Public procurement in Iraq is a major component of the national economy, cutting across nearly every area of planning, program management, and budgeting. In 2013, Iraq's approved budget was valued at US$118.3 billion, in addition to an expected US$10 billion in supplementary budget items. The lack of a clear legal framework for public procurement also discouraged foreign investment, since foreign investors were uninterested in coming to invest in Iraq if they had no type of legal assurance that bidding would be competitive, and that their bids would be treated equally and fairly. Procurement reform also becomes particularly challenging since public procurement reform means tackling corruption. Thus, it is no surprise that procurement reform in Iraq require patience, deliberativeness, and tolerance.